Application of the Extended Finite Element Method (XFEM) to Model Fatigue Crack Growth Behavior of Some Aluminium Alloys (Sebha University Conference Proceedings, 2025)
Fatigue crack growth is a critical concern in the structural integrity of aluminum components used in aerospace, automotive, and industrial applications. This research investigates the fatigue crack growth behavior of 2024-T3, AA2060, and 7075-T73 aluminium alloys using the Extended Finite Element Method (XFEM). Numerical simulations were conducted in ANSYS 19.1 to analyze the crack propagation, stress intensity factors, and fatigue life under a constant tensile load of 40 MPa across and stress ratio (R = -1). The results showed that the lowest FCGR was recorded for the 2024-T3 alloy, while the highest was for the AA2060 alloy. The lower FCGR gives the highest (Nf); 2024-T3 had the longest number of cycles to failure. This study validates XFEM as an effective tool for modeling complex fatigue crack growth scenarios and provides valuable insights for fatigue life assessment in Aluminum alloy components.